2014
DOI: 10.1021/ol500850d
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Catalyzed Radical Oxidative Coupling Reaction of Aryl Olefins with 1,3-Dithiane

Abstract: An alternative method to an iron-catalyzed radical oxidative cross-coupling reaction followed by 2-chloro-1,3-dithiane and aryl olefins for the synthesis of β-chloro substituent 1,3-dithiane products is presented. The described method has the advantage of mildness of the reaction conditions and tolerates a variety of functional groups. Preliminary mechanistic studies have confirmed the first example of a coupling of 1,3-dithiane with unactivated alkenes that proceeds via an iron-catalyzed oxidative radical int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…In our recent work on radical oxidative coupling, we reported a general method for the proposed ATRA of 2‐chlorodithiane and arylalkenes in the presence of an iron catalyst system;8a toward the further study, we discovered that O 2 is also a highly effective oxidant for dithiane radical oxidative couplings 8b. Based on these findings, we attempted to apply a similar oxidation system or metal catalyst to the coupling of phenylacetylene 1 a and 2‐chlorodithiane 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In our recent work on radical oxidative coupling, we reported a general method for the proposed ATRA of 2‐chlorodithiane and arylalkenes in the presence of an iron catalyst system;8a toward the further study, we discovered that O 2 is also a highly effective oxidant for dithiane radical oxidative couplings 8b. Based on these findings, we attempted to apply a similar oxidation system or metal catalyst to the coupling of phenylacetylene 1 a and 2‐chlorodithiane 2 .…”
Section: Methodsmentioning
confidence: 99%
“…[64] Substituted styrenes can react directly with 1,3-dithiane in the presenceo facatalytic amount of FeCl 3 (10 mol %) and N-chlorosuccinimide( NCS;1 .2 equiv; Scheme 32). [65] Both electron-rich and electron-deficient styr-enes give the desired products, whilst sterically hindered ortho-substituted aryl olefins are also suitable substrates. Substituents that contain free hydroxy groups (o-, m-, and p-styrenes) providet he main limitations to the substrate scope in this reaction, because they are unreactive under the reaction conditions.…”
Section: Radical Reactions Triggeredbyo Xidative Set By Iron(iii) Saltsmentioning
confidence: 99%
“…The oxidative radical coupling reactions have been employed to construct important carbon–halogen bond over the past decades. It was found that the carbon centered radicals with two electron‐rich sulfur atoms were enough stable to execute three‐component reactions of alkenes with 1,3‐dithianes and N ‐chlorosuccinimide (NCS) (Scheme ) . Difunctionalization of alkenes with 1,3‐dithiane, NCS, and FeCl 3 was successfully performed to afford β ‐chloro‐substituted 1,3‐dithianes in high yields.…”
Section: Construction Of C−c Bondsmentioning
confidence: 99%
“…It was found that the carbonc entered radicals with two electron-richs ulfur atoms wereenough stable to execute three-componentr eactions of alkenes with 1,3-dithianes and N-chlorosuccinimide( NCS) (Scheme 24). [19] Difunctionalization of alkenes with 1,3-dithiane, NCS, and FeCl 3 was successfully performed to afford b-chloro-substituted 1,3-dithianes in high yields. Within the reaction, NCS serves as ac hloride source anda no xidant.…”
Section: Fe-catalyzed Oxidative Addition and Functionalizationmentioning
confidence: 99%